The Role and Uniqueness of Folklore Elements in Uzbek and Turkish Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the role and uniqueness of folklore elements in Uzbek and Turkish literature, emphasizing their cultural, historical, and literary significance. Folklore, as a carrier of national identity, collective memory, and moral values, plays a pivotal role in shaping the thematic and stylistic frameworks of both literatures. The study undertakes a comparative analysis of key folklore motifs such as heroic epics (e.g., “Alpomish” and “Dede Korkut”), mythical archetypes, legends, oral poetic forms, and traditional narrative structures. It is argued that folklore in both Uzbek and Turkish literary traditions serves not only as a foundation for literary creativity but also as a means of preserving linguistic richness, social ideals, and historical continuity. Through textual analysis of representative works from classical and modern periods, the paper highlights how folklore elements are reinterpreted and adapted to reflect contemporary realities, national identity construction, and ideological messages. Uzbek literature often embeds folklore in lyrical and didactic genres, while Turkish literature integrates it deeply into both epic and realist prose. Moreover, the article examines how folklore acts as a bridge between the past and present, connecting generations and fostering cultural resilience. Special attention is given to the stylistic devices and linguistic features inherited from folklore, including repetition, rhythmic patterns, symbolism, and traditional formulas. The article also discusses the role of folklore in literary education and its relevance in postmodern reinterpretations. By synthesizing literary theory, cultural studies, and comparative methodology, this research provides a comprehensive understanding of the deep-rooted interdependence between folklore and national literature in both Uzbek and Turkish contexts. In conclusion, folklore elements in Uzbek and Turkish literature are not merely ornamental or historical artifacts, but living traditions that continue to inform, inspire, and enrich literary production. Their preservation and modern application reflect the dynamic interplay between tradition and innovation in the literary heritage of Turkic-speaking peoples.